Pesticide drift: comparing spraying systems under variable field climatic conditions - Rebelatto Muniz, Camila; Braga Pereira Braz, Guilherme; de Freitas Souza, Matheus; Marasca, Indiamara; Jorge Bernabé Ferreira, Camila; Pereira Marques, Renata; Maia Geraldine, Alaerson; Tereza Torquato Reginaldo, Lais Regina (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
Safe pesticide application must ensure efficacy in pest control while minimizing environmental and human health risks. This study investigated pesticide potential drift by comparing ground and aerial spraying systems under different climatic conditions. The research was conducted in Rio Verde, Goiás, Brazil, using a randomized block experimental design with 10 repetitions and a 2 x 2 split-plot scheme, considering spraying systems and climatic conditions as factors. Favorable and Unfavorable conditions were determined by relative air humidity, temperature, and wind speed. Aerial spraying was performed using a Cessna aircraft, while terrestrial spraying was done using a self-propelled Montana Parruda sprayer. Variables assessed included Volumetric Median Diameter (VMD), droplet density (DEN), and target coverage. Results revealed that aerial spraying has a higher drift potential, exceeding 180 m, compared to terrestrial spraying, limited to 90 m under unfavorable conditions. Although terrestrial spraying produces larger droplets, its shorter distance to the target and reduced speed minimize lateral movement, limiting drift potential. Droplet density and non-target area coverage were low for both systems, (0.1%). Under ideal conditions, aerial spraying is more efficient, but both methods require rigorous safety measures to prevent contamination risks. This study underlines the importance of considering droplet size and specific environmental conditions when choosing a spraying system, contributing to safer and more efficient agricultural practices. Highlights: Terrestrial spraying produces larger droplets which results in limited drift potential. Aerial spraying has a higher drift potential compared to terrestrial spraying. Aerial spraying is more efficient under favorable environmental conditions. For safer and more efficient agricultural practices it is important considering droplet size and specific environmental conditions.